The effect of different positively charged silver nanoparticles against bacteria, fungi and mammalian cell line. - Ahmad Gholami; Mohammad-Bagher Ghoshoon; Parisa Ghafari; Younes Ghasemi (Shiraz University of Medical Sciences, 2017)
The bactericidal efficiency of various positively charged silver nanoparticles has been extensively evaluated in literature, but there is no report on efficacy of various positive charged silver nanoparticles. The goal of this study is to evaluate the role of different positive electrical charge at the surface of silver nanoparticles on antibacterial activity against a panel of microorganisms and their biofilm activities and their cytotoxicity. Four different silver nanoparticles were synthesized by different methods, providing four different electrical surface charges (two ionic liquids (imidazolium and pyridinium) with 12 and 18 alkyl chain length) namely C12Im, C12Py, C18Im and C18Py, respectively. The antibacterial activity of these nanoparticles was tested against gram-positive (i.e., Staphylococcus aureus, Bacillus subtilis), gram-negative (i.e., Escherichia coli and Salmonella typhi) bacteria and Candida albicans as fungi. Disc diffusion and micro-dilution tests were used to evaluate the bactericidal activity of the nanoparticles according to CLSI methods. Also primary cytotoxicity assay of nanosilvers was assessed by MTT test. According to the obtained results, C12Py showed the highest bactericidal activity against all microorganisms tested. C18Im had the least and the C12Im had intermediate antibacterial activity. The most resistant bacteria were Escherichia coli. Different positive surface charge of silver nanoparticles was a significant factor affecting their bactericidal activity. Although the nanoparticles capped with pyridinium and 12 alkyl chains showed the highest level of effectiveness against the organisms tested, the silver nanoparticles capped with imidazolium and 12 alkyl chains were also potent against most bacterial species. Cytotoxicity of the silver nanoparticles was negligible.